Improving Female Students’ Academic Achievements: Special Evidence from 2nd Year Management Department Students of Bonga University, Ethiopia - Adem, Mohammed Abdulselam; Untiso, Amanuel Desalegn (International Journal of Educational Studies, 2021)
Action Research is a formative study of progress commonly practiced by teachers in schools. It enables a teacher to craft most appropriate strategy within its own teaching environment. Action research aims to contribute both to the practical concerns of people in an immediate problematic situation and to further the goals of social science simultaneously. This paper is aims to improve the academic performance of female students with special evidence from 2nd year management department of Bonga University. further, factors affecting the academic achievement of female students were examined. Finally, the role of teachers in improving female student academic performance were investigated. In doing so, the researcher adopted interview, focused group discussion and observations as data collection instruments. In addition, the researcher, prepared schedule composed of Proposed plan, action and evaluation for achieving the goals of this project. The collected data were analyzed using descriptive statistics such as mean and Paired sample T- test. The finding of this Action research project revealed that; Lack of proper Tutorial class has significant effects on female students’ achievement with average mean of 3.55, followed by lack of pear learning with mean score of 3.40. further, the overall Average Score of female students Before intervention was 3.98. but, After the researcher and course instructor made intervention which described in methodology parts the overall Average Score of female students has increased to 6.65. The researcher recommends the female students to give due consideration for their education and to read cooperatively with their colleagues. Further, Teachers should encourage female students through providing enough and timely tutorials. Finally, Bonga university shall establish female students club that actively serves all female students of the university through preparing training and conferences on which they exchange experiences with each other if possible with other universities female students.